The Influence of Tax Incentive and Environmental Concern on Electric Vehicle Purchase Intention (Case Study on Potential Customer of Chery Electric Vehicle) - Natalie, Jessica; Tri Wulandari (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2024)
The purpose of this study is to determine whether Tax Incentive and Environmental Concern have significant effect on EV Purchase Intention. This study uses quantitative data methods, and the data source is primary data. The population in this study are potential customers at PT Medan Oriental Stars. The sample in this study are potential customers that are interested in Electric Vehicles and have Tax Identification Number (NPWP) at PT Medan Oriental Stars in total of 32 respondents using purposive sampling methods. Data analysis and testing consist of validity test, reliability test, descriptive statistics, the classical assumption test, multiple regression analysis, partial hypothesis testing (T test), and simultaneous hypothesis testing (F test), and coefficient of determination test. The results of this study indicate that Tax Incentive doesn’t have significant effect on Purchase Intention of Electric Vehicle with a T count of -0,504 < T table 2,042. Environmental Concern has a partially significant effect on Purchase Intention of Electric Vehicle with a T count 5,471 > T table 2,042. Tax Incentive and Environmental Concern simultaneously have a significant effect on Purchase Intention of Electric Vehicle with a F count 18,816 > F table 3,33 and regression coefficient value of 56,5%.